Identification of microsatellites from an extinct moa species using highthroughput (454) sequence data - Allentoft, M.; Schuster, S.; Holdaway, R.; Hale, M.; McLay, E.; Oskam, C.; Gilbert, Thomas; Spencer, P.; Willerslev, E.; Bunce, Michael (Informa Healthcare, 2009)
Genetic variation in microsatellites is rarely examined in the field of ancientDNA (aDNA) due to the low quantity of nuclear DNA in the fossil record together with the lack of characterized nuclear markers in extinct species. 454 sequencing platforms provide a new high-throughput technology capable of generating up to 1 gigabases per run as short (200–400-bp) read lengths. 454 data were generated from the fossil bone of an extinct New Zealand moa (Aves:Dinornithiformes). We identified numerous short tandem repeat (STR) motifs, and here present the successful isolation and characterization of one polymorphic microsatellite (Moa_MS2). Primers designed to flank this locus amplified all three moa species tested here. The presented method proved to be a fast and efficient way of identifying microsatellite markers in ancient DNAtemplates and, depending on biomolecule preservation, has the potential of enabling high-resolution population genetic studies of extinct taxa. As sequence read lengths of the 454 platforms and its competitors (e.g., the SOLEXA and SOLiD platforms) increase, this approach will become increasingly powerful in identifying microsatellites in extinct (and extant) organisms, and will affordnew opportunities to study past biodiversity and extinction processes.